2018
DOI: 10.21522/tijph.2013.06.04.art006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B among School Adolescents in Jos, Plateau State Nigeria

Abstract: A high average prevalence rate of 11-13.7% for viral hepatitis B exists in Nigeria among the general population (National AIDS/STIs Control Program (2016). This study was the first of its type however, to examine the prevalence of hepatitis B among a specific target group, the senior secondary school students in Jos, Plateau state in Nigeria. It was conducted in six public day secondary schools located in Jos South Local Government Area, Plateau state, findings of which would help determine interventions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In a quasi-experimental study carried to investigate the barriers to access HBV testing among secondary school students in Jos, Plateau state, [11] observed that lack of awareness was the major barrier to access HBV test. There are other challenges for the attainment of the 2030 agenda for SDGs such as, unavailability of the HBV tests and lack of freedom of health decisions especially among secondary school students [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a quasi-experimental study carried to investigate the barriers to access HBV testing among secondary school students in Jos, Plateau state, [11] observed that lack of awareness was the major barrier to access HBV test. There are other challenges for the attainment of the 2030 agenda for SDGs such as, unavailability of the HBV tests and lack of freedom of health decisions especially among secondary school students [11].…”
Section: Discussionmentioning
confidence: 99%
“…In a quasi-experimental study carried to investigate the barriers to access HBV testing among secondary school students in Jos, Plateau state, [11] observed that lack of awareness was the major barrier to access HBV test. There are other challenges for the attainment of the 2030 agenda for SDGs such as, unavailability of the HBV tests and lack of freedom of health decisions especially among secondary school students [11]. Looking at the importance of students in the chain of sexually transmitted infections, there is a need to conduct a survey on the prevalence of HBV and HCV among tertiary and secondary school students in Jos, Nigeria.…”
Section: Discussionmentioning
confidence: 99%